Use of tissue samples in diagnosing diploid triploid mosaicism. Issue 12 (8th December 2022) - Mahon, Oisín; Fox, Áine; Lynch, Sally Ann; Cunningham, Katie
Abstract : Diploid triploid mosaicism (DTM) is a rare genetic condition where there is an extra haploid set of chromosomes in mosaic form. We describe an infant for whom DTM was detected antenatally through amniocentesis. Prenatal counselling suggested a guarded prognosis. The infant's phenotypic presentation and postnatal course reflect the varied presentation and prognosis associated with DTM. We highlight potential challenges in diagnosing DTM postnatally, with many having normal blood karyotype with 46 chromosomes.